Self- and other-reference in social contexts from global to local discourses - Nevala, Minna ca. 21. Jh; Palander-Collin, Minna 1967- (John Benjamins Publishing Company, 2024)
The chapters in this volume study the construction, representation and negotiation of a variety of social roles through self- and other-reference markers or the discussion of reference as a tool for identification
Keywords: Referenz -- Linguistik; Soziolinguistik; Identitätsfindung; Aufsatzsammlung